Management in oral and maxillofacial surgery during the COVID-19 pandemic: Our experience. Issue 6 (July 2020) - Barca, Ida; Cordaro, Raffaella; Kallaverja, Elvis; Ferragina, Francesco; Cristofaro, Maria Giulia
Abstract: A novel β-coronavirus (2019-nCOV), identified in Wuhan City in late December 2019, is generating a rapid and tragic health emergency in Italy due to the need to provide assistance to an uncontrollable number of infected patients and, at the same time, treat all the non-deferrable oncological and traumatic maxillofacial conditions. This article summarises the clinical and surgical experience of Maxillofacial Surgery Unit of "Magna Graecia" University (Catanzaro -Italy) during the COVID-19 pandemic and would like to provide a number of recommendations that should facilitate the scheduling process of surgical activities during the COVID-19 pandemic and reduce the risk of infection among healthcare professionals.